Specially-criminological prevention of the homicide for mercenary motives - Оберемко, Юлія Олексіївна (Problems of legality, 2016)
Objects of preventive influences with specially-criminological prevention of the homicide for mercenary motives are: the behavior of violence-prone people and unlawful acquisition of property; crime situation that adversely affects the formation of personality and leads to its formation to crime; conditions that facilitate the commission of homicides for mercenary motives and potential victims of these crimes. The questions of the specifically-criminological crime prevention have been the subject of many scientists, including: V. S. Batyrhareyeva, V. V. Golina, B. M. Golovkin, A. M. Lytvynova, A. P. Zakalyuka, V. I. Shakun and others. However, there is still no individual studies devoted to issues of specially-criminological prevention of this type of crime. It is suggested that the specially-criminological prevention of homicides for mercenary motives are sorted out with the areas: 1) identification, registration with and conducting preventive work among people who are prone to obtaining property by force; 2) limit and eliminate the negative impact of the criminal group, which contributes to the commission of homicides for mercenary motives; 3) eliminate conditions that create practical opportunities to commit homicides for mercenary motives; 4) termination of prepared or commited homicides for mercenary motives. Implementation of complex measures proposed within these areas specially-criminological prevention of homicides for mercenary motives, will contribute significantly reduce the level of crime. The article reveals the directions of specially-criminological prevention of homicides for mercenary motives. A set of measures whose implementation will contribute to the reduction of these crimes.